“Obese Equals Lazy?” Analysis of the Association between Weight Status and Physical Activity in Children - F. Kreuser; K. Kromeyer-Hauschild; A. Gollhofer; U. Korsten-Reck; K. Röttger (Journal of Obesity)
Introduction. Literature provides evidence that overweight children are more sedentary. To verify this generalized statement behavior patterns of overweight and nonoverweight children needs to be understood. Therefore, we investigated the distribution of sedentary and activity levels in a quantitative and qualitative way. Methods. Data was collected from 37 randomly selected nonoverweight and 55 overweight children. They were 8 to 11 years of age. Height and weight were measured and weight status was characterized by BMI (BMI-percentile, BMI-SDS). Daily PA (physical activity) was measured by direct accelerometry. Spare time and screen time entertainment were obtained by questionnaires. Results. The amount of time spent “passive” was significantly higher in overweight children, while nonoverweight children were more “active.” The multiple regression model shows a significant association between weight status (BMI-SDS) and activity parameters. Additionally, screen time entertainment was significantly related to BMI-SDS. Conclusion. The results support the statement that overweight children are less active than nonoverweight children. The high amount of PA seems to be an important factor to prevent overweight in children given that PA shows the highest correlation to weight status. Quantitative and qualitative measurements are needed for further analysis.